2015
DOI: 10.5978/islsm.15-or-05
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of LLLT in swelling and pain control after the extraction of lower impacted third molars

Abstract: This study demonstrates that LLLT is effective on postoperative pain and oedema accelerating healing time and reducing patients distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 19 publications
2
14
0
12
Order By: Relevance
“…In all these studies, the third molar was the extracted tooth except in one study conducted on premolar's extraction sockets. 23 PBM effectively reduced post extraction pain as shown in 16 studies 5,6,13,[15][16][17][18][19][24][25][26][27][28][29][30][31] compared with placebo. In these studies, wavelengths ranged from 650 to 980 nm.…”
Section: Study Selectionmentioning
confidence: 78%
See 1 more Smart Citation
“…In all these studies, the third molar was the extracted tooth except in one study conducted on premolar's extraction sockets. 23 PBM effectively reduced post extraction pain as shown in 16 studies 5,6,13,[15][16][17][18][19][24][25][26][27][28][29][30][31] compared with placebo. In these studies, wavelengths ranged from 650 to 980 nm.…”
Section: Study Selectionmentioning
confidence: 78%
“…11,12 A number of studies have demonstrated that PBM has an impact on the management of pain and swelling. 5,[13][14][15][16][17][18] Ferrante reported that PBM is useful for pain reduction after impacted third molar surgery. 19 In an animal study, it has been shown that PBM could reduce pain intensity, inflammation, and immunological reactions; while in human studies some factors including the type of disease, surgery, and laserrelated variables influence the outcome of PBM.…”
Section: Introductionmentioning
confidence: 99%
“…L'hémostase est assurée à la pince bipolaire ou grâce au laser comme dans le cas présenté et la plaie est suturée si nécessaire avec un fil monobrin non résorbable 5.0. Les suites opératoires sont en général simples, notamment avec l'utilisation du laser diode [4]. La prescription d'antalgiques de palier 1 est recommandée pendant 3 à 5 jours et une alimentation liquide et froide pendant 3 jours est préférable.…”
Section: Discussionunclassified
“…Le traitement repose sur une exérèse de la double lèvre à la lame froide. Le traitement de la double lèvre du SA au laser diode n'a jamais été décrit et pourrait présenter une alternative simple et non iatrogène [4].…”
Section: Introductionunclassified
“…Diode lasers have wavelengths in the near infrared range (700-900 nm) and can penetrate to a depth of 2 to 3 cm depending on the target tissue 3) . For these reasons, diode lasers can be used for TMD (Temporo-mandibular disorder) pain relief 4,5) , promoting wound healing 6,7) , cell growth 8,9) as well as soft tissue ablation with HLLT 1) . Although diode lasers have been beneficial for dental treatment in a variety of clinical situations, there is a paucity of studies reporting on the cellular mechanisms following LLLT irradiation.…”
Section: Introductionmentioning
confidence: 99%